PERAN PENYULUH TERHADAP PENANGGULANGAN FENOMENA PERKAWINAN SIRI DI CAMPALAGIAN POLEWALI MANDAR PERSPEKTIF HUKUM ISLAM - Sitti Musdalifah; Asni; Hamzah Hasan (Universitas Islam Negeri Alauddin Makassar, 2023)
The main problem in this research is what the role of extension workers is in overcoming the phenomenon of unregistered marriages in Campalagian District and Polewali Mandar Regency from the perspective of Islamic law. This research is a type of field research that describes the results of the discussion using a descriptive qualitative method with an empirical juridical approach and a Syar'i approach. The results showed that the role of counselors in overcoming unregistered marriages in Campalagian sub-district, namely carrying out counseling on marriage registration and happy families conducted by BP4 KUA and conducting socialization on the impact of unregistered marriages and the importance of a marriage registration and its negative impact on families, especially mothers and children, is expected. The community is more concerned about the registration of marriages, and extension workers convey socialization in easy-to-understand language related to religious preaching.